2020
DOI: 10.1136/annrheumdis-2019-216539
|View full text |Cite|
|
Sign up to set email alerts
|

Pragmatic randomised controlled trial of very early etanercept and MTX versus MTX with delayed etanercept in RA: the VEDERA trial

Abstract: ObjectivesWe sought to confirm in very early rheumatoid arthritis (ERA) a much greater superiority (30%) of first-line etanercept+methotrexate (ETN+MTX) over treat-to-target MTX (MTX-TT) than previously reported in ERA (14%); and explore whether ETN following initial MTX secures a comparable response to first-line ETN+MTX.MethodsPragmatic, open-label, randomised controlled trial of treatment-naïve ERA (≤12 months symptom), Disease Activity Score 28 joint (DAS28)-erythrocyte sedimentation rate (ESR) ≥3.2, rheum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
0
17
0
2
Order By: Relevance
“…Remission defined response status, aligned with the primary endpoint of the associated VEDERA RCT although holds potential weaknesses. 12 However, we also did not identify an association with cumulative burden of disease activity, nor did change in AD correlate with change in ESR or CRP (data not shown). Previous studies to report on such associations have been contradictory.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Remission defined response status, aligned with the primary endpoint of the associated VEDERA RCT although holds potential weaknesses. 12 However, we also did not identify an association with cumulative burden of disease activity, nor did change in AD correlate with change in ESR or CRP (data not shown). Previous studies to report on such associations have been contradictory.…”
Section: Discussionmentioning
confidence: 57%
“…Our study was not designed to assess for the known deleterious effects of corticosteroid 38 and non-steroidal anti-inflammatory drug (NSAID) comedication, however, equivalent corticosteroid usage across both treatment arms ensures balance in any possible interaction. 12 In summary, this is a first RCT-derived longitudinal study in a new onset, treatment-naïve ERA cohort with no history of CVD. This study demonstrated the presence of CV abnormalities at the earliest stage of RA and the ability of RA therapy to improve vascular stiffness.…”
Section: Rheumatoid Arthritismentioning
confidence: 86%
See 2 more Smart Citations
“…Methotrexate (MTX) is a rst-line therapeutic drug for the treatment of rheumatoid arthritis (RA), it is the anchor drug for disease-modifying anti-rheumatic drugs (DMARDs), and it is used throughout the world for treatment-naïve, active RA patients [1][2][3]. Approximately 30% of early RA patients achieve clinical remission with MTX monotherapy after six months treatment [4,5]. The remaining patients are classi ed as partial responders or non-responders and treatment with additional DMARDs is required according to the "treat to target" strategy [6].…”
Section: Introductionmentioning
confidence: 99%